PERAN PEMERINTAH DESA DALAM PEMBERDAYAAN KELOMPOK TANI - Ramli, Hajra; Muhiddin, Amir; Yusuf, Muh (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
This research aims to determine the role of the village government as a regulator, dynamist and facilitator in empowering farmer groups in Tawakua Village, Angkona District, East Luwu Regency. The type of research used is descriptive qualitative. The data collection techniques used were observation, documentation and interviews with a number of informants in the field. The results of this research show that the role of the village government is considered less than optimal, where the role of the government as a regulator shows that the village government does not make rules regarding the empowerment of farming communities, but the village government implements the regulations from the central government, the role of the village government as a dynamist, mentoring and training is not evenly provided to all. farmer groups, and the role of the village government as a facilitator in providing seeds, fertilizer and production facilities and infrastructure that are in accordance with the needs of the farming community